Sosialisasi Pengolahan Sampah Organik Menjadi Eco-Enzyme dan Produk Turunannya di Kawasan Ekowisata Mangrove Bagek Kembar, Sekotong, Lombok Barat - Ernawati Ernawati; Immy Sucy Rohyani; Suripto Suripto; Ahmad Jupri; Rachmawati Noviana Rahayu; Isrowati Isrowati (Jurnal Gema Ngabdi, 2023)
Environmental problems, especially waste, are still an issue that has not been resolved to date. Apart from household activities, tourist activities are also a source of waste generation. Sekotong is an area in West Lomob that is starting to develop mangrove ecotourism, one of which is Bagek Kembar mangrove ecotourism. Waste management in the Bagek Kembar mangrove ecotourism area is still not available. Garbage is only collected and some is not processed and burned. This can be caused by the lack of information and learning from managers and local communities regarding the importance of waste management. One approach to overcoming this problem is by conducting waste management outreach and training to the community. The community must be involved in planning and operating waste management activities. This community service activity consists of three stages, namely the preparation stage by conducting a location survey, the second stage by holding outreach with the aim of socializing the management and processing of waste into environmentally friendly products and the final stage is evaluating the activity by assessing the effectiveness and level of community participation in waste processing. . The method used is participatory discussion and Focus Group Discussion (FGD) combined with direct practice of processing organic waste into Eco-Enzyme and Eco-Enzyme liquid soap. The activity went well and smoothly, where the community was enthusiastic during the activity with many people asking questions and actively participating during the making of Eco-Enzyme liquid soap. It is hoped that the results of this activity will increase public awareness of waste problems and public knowledge in processing the waste produced at both household and community levels. So, the community can start and take an active role in processing waste and reducing waste thrown into the environment.